Clinical features and natural history of Spitz-Reed nevus in children. - Bonifazi, E.; Garofalo, L.; Milano, A. (European Journal of Pediatric Dermatology, 2016)
Melanoma in children is so rare that a dermatologist cannot diagnose any during his/her professional career. Spitz nevus can mimic melanoma both in its classical angioma-like or hypopigmented variant and in its pigmented variant that according to some Authors is indistinguishable from Reed nevus. In the actual report we examined 56 cases of pigmented variant or Spitz-Reed nevus (SRN) in children less than 13 years, we focused its morphological characteristics and its natural history in the child. The latter in the child looks like that one of the angioma-like variant of Spitz nevus and more generally to that of many benign proliferations of childhood in which an initial proliferative phase is followed by a phase with prevailing regressive phenomena.